1976
DOI: 10.1093/ajcn/29.6.604
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional aspects of high-altitude exposure in women

Abstract: The nutrient intake and urinary excretion characteristics of eight young university women were studied over a 4-day period at low altitude (140 m) and subsequently over a 7-day sojourn on Pikes Peak (4,300 m). High-altitude exposure was associated with a transient decrease in the consumption of protein, carbohydrate, fat, sodium, calcium, phosphorus, vitamin A, riboflavin, thiamin, and niacin and a more sustained decrease in the consumption of potassium and ascorbic acid. In most instances minimal values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
3
20
1
Order By: Relevance
“…The reduced energy intake at 4559 m confirms previous findings at similar altitudes 388 where both males and females were shown to reduce their energy intake by more 389 than 30% after ascent to 4300 -5100 m [15,21,33,40]. The present study extends 390 these findings by providing a systematic analysis of certain factors that may 391 contribute to the energy intake reducing effect of hypoxia following rapid ascent to 392 16 high altitude.…”
Section: Energy Intake 387supporting
confidence: 78%
“…The reduced energy intake at 4559 m confirms previous findings at similar altitudes 388 where both males and females were shown to reduce their energy intake by more 389 than 30% after ascent to 4300 -5100 m [15,21,33,40]. The present study extends 390 these findings by providing a systematic analysis of certain factors that may 391 contribute to the energy intake reducing effect of hypoxia following rapid ascent to 392 16 high altitude.…”
Section: Energy Intake 387supporting
confidence: 78%
“…Therefore, our data do not agree with those of Hannon et al [10] who found an increase in carbohydrates intake in 8 young women over a 7-day period stay at 4,300 m, and with those of Rose et al [33] who studied subjects during progressive decompression in a hypobaric chamber and observed a reduc tion in carbohydrates and an increase in fat consumption.…”
Section: Discussioncontrasting
confidence: 99%
“…It has been demonstrated that the weight loss during the mountaineering expedition could be due to dehydration [6,26]; during acclimatization a decrease of intra-and extra cellular water occurs and this may result in a weight change of about 1-2 kg [5,10,17], but as we evaluated the body weight and body composition at the beginning of the study and 7 days after return to sea level, we can exclude that the weight loss could have been caused by water loss. This fact is very important in the analyses of our results because we determined body composition changes by bioelectrical impedance analysis and Fulco et al [8] dem onstrated that it does not work in the determi nation of changes of fat-free mass at altitude for the interference of water loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis a query of experienced practitioners in Peru, Fitzmaurice, (1920) suggested that women suffered less AMS then men, but suggested that they did so partially because women lead a less "strenuous life" than males and were more "abstemious in their habits." Acute mountain sickness symptoms measured in eight young women living on the summit of Pikes Peak for 10 weeks, when compared to AMS symptoms in males on Pikes Peak in separate studies, suggested that women possibly are less susceptible to AMS (Hannon, et al, 1976;Harris, 1966). Likewise, Krämar and colleagues (1983) felt that the AMS they observed in seven women climbers on Ana Purna in the Himalayan mountains was less severe than that reported in 12 soldiers on Pikes Peak in Colorado (Kobrick and Sampson, 1979).…”
Section: Introductionmentioning
confidence: 99%